ISOLASI DAN KARAKTERISASI MIKROBA PELARUT FOSFAT - Prihastuti, (Matematika dan Sains, 2009)
The acid dry soils of Central Lampung had high biodiversity of the phosphate-solubility microbial. There were 65 isolates of the microbial, consisted of 44 of mold and 21 of bacterial isolates, obtained. The present research purposes to characterize these microbial, including colony morphology, respiration, gram painting and formation of clear zone at the Pikovskaya medium enriched with P from Ca3(PO4)2 and sediment. Results of the trial revealed that the index value of these microbial were immeasurable by 2.40-6.25 and 1.05-3.50 for bacterial and mold at the Pikovskaya medium enriched by P from Ca3(PO4)2. At the same medium enriched with P sediment, the index values were 1.40 -3.30 and 1.07-2.08 for bacterial and mold.3(PO4)2 and sediment. Results of the trial revealed that the index value of these microbial were immeasurable by 2.40-6.25 and 1.05-3.50 for bacterial and mold at the Pikovskaya medium enriched by P from Ca3(PO4)2. At the same medium enriched with P sediment, the index values were 1.40 -3.30 and 1.07-2.08 for bacterial and mold.